MORPHOLOGICAL CHANGES ON THE DANUBE DELTA BIOSPHERE RESERVE COAST – ACTUAL SYNTHESIS - PETRE GÂŞTESCU; ION GRIGORAŞ (Revue Roumaine de Géographie)
The Romanian Black Sea coastline covers 245 km. In terms of genesis and morphology, this coastline can be roughly divided into two sectors: accumulation of marine levees in the north, from Musura Stream at the Ukrainian border to Cape Midia (166 km); abrasion in the south with high cliffs, from Cape Midia to Vama Veche; the Bulgarian border (79 km). The article analyzes the northern sector corresponding to the delta front (Danube Delta Biosphere Reserve coast). This sector was created as a result of accumulation processes, the north-south coastal marine currents, moving the river alluvia blocked the river mouth forming the Danube Delta and Halmyris lagoon, the whole becoming Razim-Sinoie Lake Complex. This marine shore sector, due to the contribution of river alluvia, is characterized generally by the advance in the marine space, but the current conditions (reducing the volume of sediments from the Danube, marine minitransgression and anthropogenic interventions (by the dams raised at the mouth of the Sulina branch and Cape Midia) generate shoreline retreat in some areas. To identify portions of advancement and retreat, and setting the corresponding annual rates, existing topographic map series for a period of over 150 years, hydrographic measurements for 30 years and series of satellite images starting from 1975 were used.